Perancangan Sistem Informasi Pengolahan Nilai Rapor Berbasis Web Pada SMK Negeri 1 Purworejo - Wahyu Setyo Prabowo; Candra Agustina (Jurnal Khatulistiwa Informatika, 2017)
ABSTRACTUse of information technology is not only limited in the workplace but also in other aspects of life such as school. Use of information technology is expected to improve the quality of education, improve the efficiency of time and resources for schools in both the teaching and learning activities and school administration as in the making of the report card. SMK Negeri 1 Purworejo requires the existence of an information system to support and simplify the making of the student’s grades report. Therefore, the author make the Final Assignment concerning with the information system of the grades processing at SMK Negeri 1 Purworejo. Unavailability of information systems in accordance with the learning process is running causes are still some gaps in the activities of preparing reports such as lack of effective work, the slowness of the process of drafting, until about the time and cost needed. Based on research, literature, and interviews that have been done, then designed an grades processing information system using waterfall method becomes a solution to resolve the existing problems. Information system of grades processing simplify teachers, homeroom, or teaching part in data processing and students’s grade for preparing reports and support the other administrative activities as well as the teaching and learning process. Key Words: Design of Information Systems, Grades Processing System, Student’s Grades Report of SMK Negeri 1 Purworejo